SMART HOME DESIGN IN INDONESIA - Ardiani, Yanita Mila (Program Studi Arsitektur Fakultas Teknik Universitas Katolik Widya Mandira, Kupang, 2018)
The more the times, the more people want to get closer to the speed of getting information. Achieving information today is facilitated by the progress of technology. The case in living in a house, now has been present tools that we can guide from our gadgets even though the location is very far from where we live. Some of these tools can be installed in the home, and there is a need for a standard and the ways in which a home can be fully integrated with the tools.With these smart home tools , we can control our home by distance. The safety , the entertainment, the smart comfort living feeling , we can achieve in the smart home design. The smart home is the home that fulfill with smart tools to make our life easier with less cable and fully supported by wifi and internet. In the smart home like this, our life much more simple, and easier, and controlled well. This research try to collect the tools that can be put in the smart home and the room and spaces in the home that supported. The Research method is using qualitative methods, with experiments. The tools for Smart home standardization is used in the experiments, so that we can gain spaces that needed in the smart home design. So, the result of this study is to find the smart home typhology that is using the tools in the smart home standards. Keywords: smart, home, room